A new approach to the prediction of tool wear - Cherry, J. (College of Aeronautics, 1967)
Tool life is of major concern for economical production in the metal cutting industries and a simple method of predictive the tool wearability of materials would be of considerable value in enabling optimum cutting conditions to be determined. It has been shown that tool life for minimum cost Der piece = - 1)K where ‘n’ is the exponant, in the speed/life relationship VT - 11 = C. Since I n' is substantially constant for a given tool material and chip thickness, and K is constant for given operating conditions then the life of the tool (T) has an unique value under these circumstances. Also since tool life (T) will be determined by a specific magnitude of tool wear, a simple method by which the time to arrive at this criterion could be predicted would be very useful. In the experimental work to be described it has been possible from simple cutting tests to predict tool wear over a limited range of conditions— Much more extensive research is required to establish the range of the technique.